VALIDITY OF LAND SALE AND PURCHASE DEED IN TRANSACTIONS WITH UNPAID BALANCE (Law Research Review Quarterly, 2025)
This study aims to examine the legal validity of the Deed of Sale and Purchase (AJB) of land in transactions where the buyer has not fully settled the payment. This phenomenon frequently occurs in land practices in Indonesia and raises legal concerns regarding the legal strength of AJB as an authentic deed made by a Land Deed Official (PPAT), especially in the case of breach of contract. The research focuses on two main aspects: the validity of AJB in incomplete payment transactions under agrarian law and PPAT regulations, and the legal mechanism for its cancellation and protection for aggrieved parties. A normative legal approach is used by analyzing statutory regulations, legal principles, and relevant court decisions. The findings show that while AJB remains formally valid if procedural requirements are fulfilled, it may be materially flawed when the payment condition as a substantive requirement is unmet. Cancellation of AJB may be pursued through a civil lawsuit for breach of contract, with the burden of proof placed on the seller. This study recommends strengthening regulations on payment verification by PPAT and incorporating breach of contract clauses in preliminary agreements to enhance legal protection and certainty in land sale transactions.